2013
DOI: 10.1007/s11420-013-9349-5
|View full text |Cite|
|
Sign up to set email alerts
|

Arthrodesis after Infected Revision TKA: Retrospective Comparison of Intramedullary Nailing and External Fixation

Abstract: Our study supported the existing literature and found that reinfection after revision TKA can be effectively treated with arthrodesis. In presence of massive bone loss, we recommend arthrodesis with IM nail used as an endoprosthesis, without bone-on-bone fusion, to produce a stable and painless knee, while preserving the limb length. Use of an IM nail allowed us to get a better functional result than EF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Actually, an excess rate of re-infection after IM nail arthrodesis became evident once outlier studies were dropped off from the meta-analysis. Increased risk of recurrent infection with IM nailing as compared to EF arthrodesis has been previously reported [ 9 , 10 ], even though this finding is not supported by one recent meta-analysis [ 11 ]. Overall, these results suggest caution if the use of IM nailing is planned in difficult-to-treat PJIs (i.e.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Actually, an excess rate of re-infection after IM nail arthrodesis became evident once outlier studies were dropped off from the meta-analysis. Increased risk of recurrent infection with IM nailing as compared to EF arthrodesis has been previously reported [ 9 , 10 ], even though this finding is not supported by one recent meta-analysis [ 11 ]. Overall, these results suggest caution if the use of IM nailing is planned in difficult-to-treat PJIs (i.e.…”
Section: Discussionmentioning
confidence: 95%
“…The remaining 26 articles [ 5 , 10 , 12 , 13 , 16 37 ] were included in the meta-analysis. Two of these [ 10 , 22 ] were retrospective studies comparing outcomes of nail and EF arthrodesis. Hence, data from 18 and 10 studies were used for the assessment of surgical results of knee arthrodesis with IM nail and EF, respectively (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[85] found that functional outcome scores and LLD were significantly better in the IMN group but with higher rates of persistent infection. There was no significant difference in pain scores between both groups [85]. Van Rensch et al .…”
Section: Methodsmentioning
confidence: 99%